MEMBANGUN RELASI DI ATAS ZAWIYAH - Otong Surasman (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2019)
In this modern era, even though advances in technology are increasingly advanced and communication tools are increasingly sophisticated, there is something missing that is forgotten by most humans. In fact, what is even more sad is the loss of specialties in performing prayer services, which are carried out by Muslims today. As the barometer is so very simple, the majority of Muslims today Al-Qur'an illiteracy reaches 65% more and both Muslims are still under ignorance and poverty, which shows that Muslims are not united in solving the problems of the people. Each of them prioritizes their personal and group interests, compared to resolving common interests. One very important effort to build a people, in order to achieve success in performing prayer services, is able to build the people's economy in eradicating poverty and ignorance, then start building relationships with Allah SWT above Zawiyah. This is a means of control which at the same time begs for guidance to Allah SWT, so that every problem faced by Muslims and the public is given a solution to the solution.